2017
DOI: 10.1159/000481435
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Is Increased in Nasal Polyposis and after Stimulation with <b><i>Staphylococcus aureus</i></b> Enterotoxin B

Abstract: Background: Chronic rhinosinusitis with nasal polyposis (CRSwNP) is an inflammatory disease associated with lymphoid aggregates and local IgE production related to Staphylococcus aureus enterotoxins. T-follicular helper cells and their effector cytokine interleukin (IL)-21 play an important role in germinal center proliferation. Methods: IL-21 was determined on the mRNA level by qPCR in nasal tissue of 3 groups of patients: control (n = 17), chronic rhinosinusitis without nasal polyposis (CRSsNP; n = 23), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…For CRSsNP patients, IL‐21 was the only cytokine correlated with any SNOT‐22 domain (Extranasal Rhinologic Symptoms, R s = 0.41, p = 0.01). The literature is sparse with respect to the role of IL‐21 in CRSsNP; however, work by Calus et al in CRSwNP patients showed upregulation of IL‐21 in response to Staphylococcus aureus enterotoxin, which suggests that mucus IL‐21 levels may be a marker of bacterial exposure. Patients without polyps were also observed to have significant correlations between IFN‐γ, IL‐12, IL‐17A, IL‐21, and global QoL metrics, representing a different inflammatory milieu than what was observed in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…For CRSsNP patients, IL‐21 was the only cytokine correlated with any SNOT‐22 domain (Extranasal Rhinologic Symptoms, R s = 0.41, p = 0.01). The literature is sparse with respect to the role of IL‐21 in CRSsNP; however, work by Calus et al in CRSwNP patients showed upregulation of IL‐21 in response to Staphylococcus aureus enterotoxin, which suggests that mucus IL‐21 levels may be a marker of bacterial exposure. Patients without polyps were also observed to have significant correlations between IFN‐γ, IL‐12, IL‐17A, IL‐21, and global QoL metrics, representing a different inflammatory milieu than what was observed in CRSwNP.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al and Calus et al reported a higher frequency of IL‐21 + CD4 + T cells locally in patients with CRSwNP than in control subjects 113,122 . Calus et al 122 further revealed that polyp CXCR5 + CD4 + T cells could induce the differentiation of naïve B cells into plasmablasts in vitro. Zhang et al 112 observed a significant expansion of CXCR5 + T FH cells in nasal polyps in comparison to those in the inferior turbinate mucosa from control subjects.…”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 96%
“…IgE and IgD are suggested to activate mast cells to drive local eosinophilic inflammation, and IgG can contribute to the activation of classical complement pathways in nasal polyps 115,120,121 . Xiao et al and Calus et al reported a higher frequency of IL‐21 + CD4 + T cells locally in patients with CRSwNP than in control subjects 113,122 . Calus et al 122 further revealed that polyp CXCR5 + CD4 + T cells could induce the differentiation of naïve B cells into plasmablasts in vitro.…”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 99%
“…Staphylococcal enterotoxin B has also been shown to regulate T follicular helper cells in nasal polyps by increasing the amount of IL-21 and IL-21 positive T cells in surgical sinus tissue stimulated with SEB ex vivo [24]. Takeda and colleagues have demonstrated that S. aureus is not the only bacteria that stimulate T H 2 inflammation in nasal polyp tissue, however.…”
Section: Staphylococcal Toxins and Crsmentioning
confidence: 99%